DIROFILARIA GENUS HELMINTHES IN KARAKALPAKSTAN CONDITIONS ARE ENDOPARASITS OF DOG-LIKE - Atajonova, Malohat Khamzaevna (SCIENCE and SOCIETY, 2026)
In the conditions of Karakalpakstan, during research conducted between 2023 and 2026, the infection of animals with nematodes of the genus Dirofilaria was established. Based on the results of complete and incomplete helminthological studies of 71 samples, Dirofilariae were identified in 26 animals (36.6%). Among the examined animals, Dirofilaria helminth infection was observed in domestic dogs: 7 out of 23 individuals (30.4%), jackals 11 out of 29 individuals (37.9%), and foxes 8 out of 19 individuals (42.1%).
Keywords: Dirofilaria; D.immitis; D.repens; invasion extensiveness; invasion intensity; Aedes; Culex